Сравнение систем скольжения в монокристаллах меди при деформации сжатием и трением - Чумаевский А. В.; Беляев С. А. Сергей Александрович; Лычагин Д. В. Дмитрий Васильевич; Алфёрова Е. А. Екатерина Александровна; Тарасов С. Ю. Сергей Юльевич; Колубаев Е. А. Евгений Александрович (2012, 2012)
Заглавие с экрана